2014
DOI: 10.1007/s40012-014-0040-x
|View full text |Cite
|
Sign up to set email alerts
|

Banking websites in India: an accessibility evaluation

Abstract: Accessibility refers to making websites usable for people of all types of abilities and disabilities, regardless of what browsing technology they are using. Since the web is an important resource of information for millions of people at all levels, accessible websites can help people with disabilities too to participate and contribute more actively in society. The objective of this study is to analyze the status of accessibility of banking websites as it allows people with disabilities to be independent and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…With these devices and access to the internet, the disabled find it difficult to access much of the information on website due to lack of accessibility. The same is applicable even to people without disabilities, who are also constantly faced with usability issues [26]. Research has shown that the most websites are not providing adequate levels of accessibility to both able and disabled persons [27].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…With these devices and access to the internet, the disabled find it difficult to access much of the information on website due to lack of accessibility. The same is applicable even to people without disabilities, who are also constantly faced with usability issues [26]. Research has shown that the most websites are not providing adequate levels of accessibility to both able and disabled persons [27].…”
Section: Related Workmentioning
confidence: 99%
“…They also detected the main weaknesses of the web pages assessed. [26] also evaluated the accessibility of Indian banking website using the conformance method and deduced that all the website had one or more accessibility issues which implies that none of the websites were accessible.…”
Section: Related Workmentioning
confidence: 99%
“…Nouman (2012) examined the accessibility issues of different financial websites of Pakistan. Kaur and Dani (2014) has conducted the study to find some common accessibility errors among banking websites according to WCAG 2.0 in India.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…A study of 48 Indian banking websites [32] was undertaken in 2014, testing the sites for accessibility using both WCAG 1.0 [33] and WCAG 2.0 [34]. Accessibility of the banking websites was low: only 25 % conformed to the minimum conformance level with respect to WCAG 1.0 (Level A), and none conformed to the minimum conformance level with respect to WCAG 2.0.…”
Section: Topic 2: Cross Cultural Accessibility Issues In Indiamentioning
confidence: 99%